Re-actualization of Herritage of Surabaya in Social Studies Learning - Hermawan, Eko Satriya (Universitas Negeri Surabaya, 2018)
Development of IPS learning media is still limited to the use of maps and power points, developed by teachers and students themselves. Teachers realize that in learning social studies (IPS) is needed the use of media learning, but because of the limitations of media owned schools so they rarely use the media as a supporter of the learning process. In addition to factors of facilities and infrastructure is also limited ability of teachers in making media and cost factors and time. This research used reseach and development (R & D) approach, which was conducted in Surabaya. The result obtained showed the characteristics of IPS education as a synthetic discipline. IPS education not only synthesizes the concept of relevant concepts between educational sciences and the social sciences but also the purpose of education and development as well as social problems in social life will be a consideration of educational materials IPS. That the identity and context of children's social and culture plays an important role in the development of social studies.